2006
DOI: 10.1016/j.neurobiolaging.2005.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Regionally specific atrophy of the corpus callosum in AD, MCI and cognitive complaints

Abstract: The goal of the present study was to determine if there are global or regionally specific decreases in callosal area in early Alzheimer's disease (AD) and mild cognitive impairment (MCI). In addition, this study examined the corpus callosum of healthy older adults who have subjective cognitive complaints (CC) but perform within normal limits on neuropsychological tests. We used a semi-automated procedure to examine the total and regional areas of the corpus callosum in 22 patients with early AD, 28 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
77
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 36 publications
16
77
2
2
Order By: Relevance
“…Since neuropsychological measures were in the normal range, these associations may reflect an early indicator of cognitive impairment becoming clinically evident only with further illness progression. On the other hand, callosal abnormalities did not correlate with scores of the CVLT long delay, mostly linked with early Alzheimer's disease (Wang et al, 2006). This might argue against the hypothesis that patients with late-onset depression are at increased risk of developing dementia.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Since neuropsychological measures were in the normal range, these associations may reflect an early indicator of cognitive impairment becoming clinically evident only with further illness progression. On the other hand, callosal abnormalities did not correlate with scores of the CVLT long delay, mostly linked with early Alzheimer's disease (Wang et al, 2006). This might argue against the hypothesis that patients with late-onset depression are at increased risk of developing dementia.…”
Section: Discussionmentioning
confidence: 81%
“…If these previous investigations are interpreted to be signs of different causes or risk factors for depression based on age at onset, greater splenium thinning in late-than early-onset depression might indeed point to more prominent atrophic or neurodegenerative processes in temporal connections, possibly reflecting higher risk for cognitive impairment and dementia conversion in the future (Geda et al, 2006;Salloway et al, 1996;Schweitzer et al, 2002;van Ojen et al, 1995). Indeed, regionally specific posterior callosal atrophy has been reported in mild Alzheimer's disease (Lyoo et al, 1997;Wang et al, 2006;Yamauchi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies investigated patients with fewer heterogeneous clinical features, such as those affected by mild or moderate AD, and they reported discrepant results. More specifically, while some studies on mild AD found atrophy in the posterior callosal subregions (isthmus and splenium) [9,11,13,19], others found no atrophy in callosal regions [45,58]. As far as we know, there is only one study [59] on moderate AD patients that describes a reduction of the anterior body, mid body, and isthmus in AD patients compared with HC.…”
Section: Region Of Interest Studiesmentioning
confidence: 99%
“…The corpus callosum (CC) has been implicated in this process [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In particular, it has been suggested that callosal atrophy in AD is the anatomical correlate of Wallerian degeneration of commissural nerve fibers.…”
Section: Introductionmentioning
confidence: 99%